Global health training among U.S. residency specialties: a systematic literature review. Issue 1 (1st January 2017) - Hau, Duncan K.; Smart, Luke R.; DiPace, Jennifer I.; Peck, Robert N.
ABSTRACT: Background: Interest in global health training during residency is increasing. Global health knowledge is also becoming essential for health-care delivery today. Many U.S. residency programs have been incorporating global health training opportunities for their residents. We performed a systematic literature review to evaluate global health training opportunities and challenges among U.S. residency specialties. Methods: We searched PubMed from its earliest dates until October 2015. Articles included were survey results of U.S. program directors on global health training opportunities, and web-based searches of U.S. residency program websites on global health training opportunities. Data extracted included percentage of residency programs offering global health training within a specialty and challenges encountered. Results: Studies were found for twelve U.S. residency specialties. Of the survey based studies, the specialties with the highest percentage of their residency programs offering global health training were preventive medicine (83%), emergency medicine (74%), and surgery (71%); and the lowest were orthopaedic surgery (26%), obstetrics and gynecology (28%), and plastic surgery (41%). Of the web-based studies, the specialties with the highest percentage of their residency programs offering global health training were emergency medicine (41%), pediatrics (33%), and family medicine (22%); and the lowest were psychiatry (9%), obstetrics and gynecology (17%), and surgery (18%). The most common challenges were lack of funding, lack of international partnerships, lack of supervision, and scheduling. Conclusion: Among U.S. residency specialties, there are wide disparities for global health training. In general, there are few opportunities in psychiatry and surgical residency specialties, and greater opportunities among medical residency specialties. Further emphasis should be made to scale-up opportunities for psychiatry and surgical residency specialties.